1998
DOI: 10.1542/peds.102.6.1437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Maternal Perceptions of an Updated Model of Perinatal Care

Abstract: We conclude that the revised model of perinatal care in this health maintenance organization medical center improved clinical outcomes and maternal satisfaction for low-risk mothers and newborns without increasing costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Although 88% of all mothers in this study initiated breastfeeding, 19% of those who started breastfeeding had stopped by 14 days after delivery. These findings are similar to those in a previous study in this HMO 23 and highlight the need for additional research on breastfeeding promotion. One in 5 mothers had depressive symptoms on the telephone interview at 14 days' postpartum; this was higher than the 9% reported in a previous study using telephone surveys at 3 weeks' postpartum in a Massachusetts HMO.…”
Section: Clinical and Legislative Contextsupporting
confidence: 89%
“…Although 88% of all mothers in this study initiated breastfeeding, 19% of those who started breastfeeding had stopped by 14 days after delivery. These findings are similar to those in a previous study in this HMO 23 and highlight the need for additional research on breastfeeding promotion. One in 5 mothers had depressive symptoms on the telephone interview at 14 days' postpartum; this was higher than the 9% reported in a previous study using telephone surveys at 3 weeks' postpartum in a Massachusetts HMO.…”
Section: Clinical and Legislative Contextsupporting
confidence: 89%
“…Another study of 926 low-risk vaginally delivered infants discharged at less than 48 hours identified 27 re-hospitalizations (2.9%) within the first 2 weeks of life. [23] This rate was is in keeping with our rates of re-admission to a pediatric hospital ward or PICU and was within the range of several studies. [242526] Moreover, Liu et al .…”
Section: Discussionsupporting
confidence: 88%
“…Several economic analyses based on cohort studies or case series have concluded that the economic value of the resources released by early postnatal discharge are not offset by increased costs to other sectors of the health service or the wider economy 10–20 . However, in addition to basing assessments of the efficacy of early postnatal discharge policies on observational evidence, these economic analyses were characterised by a number of methodological limitations.…”
Section: Introductionmentioning
confidence: 99%